Agricultural mechanization in transition farming : a case study in Vietnam - Tran Duc Cuong; Singh, Singh, Singh, Gajendra; Salokhe, Vilas M.; Clough, D. Gee; Gupta, C.P.; The Government of Netherlands (Bangkok : Asian Institute of Technology, 1994)
This study assesses the current status, trends, policy implications and development constraints related to farm mechanization in Vietnam in a transition farming period. The effects of the changes to agricultural mechanization are discussed. The data collected show that low level of mechanization is one of the factors responsible for the low productivity in agriculture. A field study carried out in Cam Dong cooperative pointed out that small farm size, low farm income and limited purchasing ability are the main constraints to mechanization. At present animal draft and human labor should be the main power sources. Public services need to be enhanced to meet the demand of draft power for the small holdings. Redesign and modification of imported mechanization technology are the main requirements of farm machinery manufacturing . Proposed direction of mechanization are the spread of mechanization to small farmers through public services, and extension of mechanization to large and specialized farms. Successful mechanization will require changes in socio-economic conditions in which the government policy is the most important factor.
Thesis (M.Eng.) - Asian Institute of Technology, 1994
A Thesis Submitted in Partial Fulfillment of the Requirements for the Degree of Master of Engineering.
Keywords: Farm mechanization -- Vietnam